The effects of skin moisturizers using electrical impedance spectroscopy - Nguyen, Son Thanh (2016)
Skin Electrical Impedance Spectroscopy (EIS) is a method that involves the injection of an AC current into human tissue and measurement of the resulting voltage drop. By measuring the tissue over a range of frequencies, the impedance spectrum can then be used to detect changes in the underlying nature of the skin tissue. One potential application is in monitoring the effects of over the counter products such as skin moisturisers on human skin. This can be useful for cosmetics companies in new product development where users of the cosmetic product could use such a device in their own home. A low cost, portable, custom-made bio-impedance analyser based on a four-point probe sensor has been constructed for measuring the skin impedance over short and long time periods. Long term measurements are motivated by manufacturer claims that the effects of moisturisers last up to 24 hours and hence a custom made device has been developed to carry out long term monitoring. The system is based around a dsPIC33F board that contains a DSP processor, Analogue Frontend and analogue stimulus all connected to a 4-point probe sensor. 100µA AC current (according to Medical Standard 60601-1) is passed to the skin through two outer probes and a voltage drop measured across the two inner probes. A DSP controls the analogue frontend, processes the measured data and transfers data to a PC for real time display. The portable custom-made device is validated against a Solartron 1260 + 1294 impedance analyser and achieved a within 5% error. Four different commercial skin creams: Bio-oil, Nivea, Palmer’s Olive Butter and Cocoa Butter have been investigated. Under controlled environmental conditions, four kinds of cream were applied to an allocated area of the arm for 1 minute. The EIS was then measured for up to 5 hours on these regions by the four point probe sensors captured by the custom-made device. Nivea, Cocoa Butter and Olive Butter have a similar response as they are type II humectants which attract water from deeper dermis to the stratum corneum. Bio oil however, can be classified as a type I occlusives as it blocked water vaporized from stratum corneum. The Impedance results can discriminate between Bio-oil/ Bare skin (Type I) and the other three Type II moisturizers (Nivea, Olive and Cocoa). This discrimination is appointed in two clear features: firstly, the impedance values from the type II creams have a much reduced variability when compared to the bare skin and Bio-oil; secondly, the plots of R versus X showed for the Type II creams to have a non “constant phase element” dominance whilst bare skin and Bio-oil showed no such behavior. Phase results demonstrated additional capacitance effects of Bio oil compared to other moisturizers. Simulation models are provided to compare with these practical results with the model fitting process.